2014
DOI: 10.1111/1748-8583.12041
|View full text |Cite
|
Sign up to set email alerts
|

Who is considered an ‘older worker'? Extending our conceptualisation of ‘older’ from an organisational decision maker perspective

Abstract: A refinement of the construct of age, specifically ‘older’, is recognised as a critical measurement concern for experts in both ageing research and policy formation. In this context, we set out to both chronologically define an ‘older worker’ and to identify on what basis the age of ‘older’ is determined. In doing so, we draw on open‐ended survey data (collected in 2011) from a sample of 407 organisational decision makers across all industries in Ireland. Our focus was specifically on the perspective of organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 31 publications
0
54
0
1
Order By: Relevance
“…Although they technically do not fall under the standard rubric for “aging” research, these service workers remain above the typical age for service workers in industry. Indeed, managers in retail and hospitality industries reported that their definition of “older worker” was actually fairly young because workers in their sectors tend to skew much younger (McCarthy, Heraty, Cross, & Cleveland, ). Regardless, the findings here do present implications for adult development (i.e., age‐related changes that occur as adults progress from young adulthood through middle adulthood to older adulthood) but not directly for adults in late life per se.…”
Section: Discussionmentioning
confidence: 99%
“…Although they technically do not fall under the standard rubric for “aging” research, these service workers remain above the typical age for service workers in industry. Indeed, managers in retail and hospitality industries reported that their definition of “older worker” was actually fairly young because workers in their sectors tend to skew much younger (McCarthy, Heraty, Cross, & Cleveland, ). Regardless, the findings here do present implications for adult development (i.e., age‐related changes that occur as adults progress from young adulthood through middle adulthood to older adulthood) but not directly for adults in late life per se.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to use the cutoff of 50 years to distinguish older workers from younger workers. Even if there is little consensus on the chronological age (or ages) at which an "older worker" is defined, a number of previous studies have used 50 years old as cut-off (McCarthy et al, 2014) and, furthermore, according to managers' opinion, the "limit of employment" seems to be 50 years (see, Karpinska et al, 2013). Based on previous findings, which showed that the same age stereotypes are shared by people of different ages, we expect that:…”
Section: Age Stereotypes In the Workplacementioning
confidence: 99%
“…However, age norms are fluid and reflect not only chronological age bands, but are shaped by societal expectations and the sectoral context. McCarthy et al (2014) suggest that decision-makers in organizations consider workers as 'older' from the chronological age of 52; however, in hospitality, the descriptor 'older' applies to people at a younger age than in other sectors (Barron et al 2014;Lucas 2007), across different national contexts. Ageist attitudes are revealed in management attitudes towards older employees in Norway (Furunes and Mykletun 2007), and in the United Kingdom, a bar manager may be considered 'too old' at the age of 30 (Nickson and Warhurst 2007).…”
Section: Age Norms In Hospitality Employmentmentioning
confidence: 99%